Active power filter control strategy based on repetitive quasi-proportional resonant control with linear active disturbance rejection control - Yifei Gao; Liancheng Zhu; XiaoYang Wang; Hongshi Wei; Xiaoguo Lv (PLoS ONE, 2025)
Active power filter (APF) is a new type of harmonic mitigation device, and its harmonic mitigation capability mainly depends on the control strategies of current inner loop and voltage outer loop. Traditional proportional integral (PI) control methods cannot track harmonic currents without steady-state error, thereby it leads to the poor tracking accuracy of the harmonic current and is difficult to achieve high-performance harmonic compensation. Thus, in this paper, a repetitive quasi-proportional resonant (QPR) with linear active disturbance rejection control (LADRC) is proposed. Firstly, QPR control is introduced to replace PI control. QPR control can eliminate steady-state error and realize no static error tracking of harmonic current. Meanwhile, QPR control can coordinate control of various frequency components and enhance APF’s ability to suppress specific harmonics. Then, the introduction of repetitive control optimizes the QPR control, so that the dynamic performance of the system does not change while further improving the tracking accuracy of the APF system for harmonic current. Finally, LADRC control is used to observe and compensate for the coupled parts of the system. Thereby, it can achieve high-performance decoupling without adding additional sensors. In addition, in order to ensure the stability of the DC-side voltage and enhance its dynamic performance, this paper also designs a voltage outer loop controlled by QPR. The proposed method is verified by real-time digital simulation system (RTDS). The simulation results show that compared with the double closed-loop PI control, the repetitive quasi-proportional resonant with linear active disturbance rejection control (repetitive QPR-LADRC) and QPR double closed-loop control proposed in this paper can not only increase the harmonic current tracking accuracy of APF system, but also improve the dynamic performance of APF system and significantly enhance the harmonic suppression ability of APF.